Channel initiation in the semiarid Colorado Front Range - Henkle, Jameson E., author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Bledsoe, Brian, committee member (Colorado State University. Libraries, 2010)
The channel head, defined as the upstream boundary of concentrated water flow and sediment transport between definable banks, represents the transition from hillslope processes to fluvial processes. The ability to delineate the location along a slope at which channels initiate is important for understanding hydrologic and geomorphic processes governing headwater streams. Studies demonstrating an inverse relationship between either contributing drainage area (A) and local valley slope {6) or basin length (L) and 6 for channel heads come primarily from regions with humid climates. Seventy-eight channel heads were mapped in the headwaters of the Cache la Poudre River and the North St. Vrain Creek in the semiarid Colorado Front Range. Multiple field sites were chosen along both rivers to account for variability due to aspect and elevation. Surface topographic parameters were measured in the field and analyzed to test the hypothesis that surface processes control channel initiation in this region. Although simple linear regressions indicate a poor inverse relationship between A and L and no relationship between L and (9, multiple regressions indicate that surface topographic parameters explain over half the variability in the location of channel heads. This suggests that surface processes exert an influence on channel initiation, but do not explain as much of the variability as observed in previous studies from wetter regions. A threshold of erosion necessary to initiate a channel was observed at approximately 10,000 for .4, although values as high as 600,000 were mapped for some channel heads. Variation within the study area correlated with elevation, which is a proxy for differences in volume and type of precipitation; sites at lower elevation with less precipitation, but more intense convective rainfall, tend to have smaller contributing area and basin length. Aspect did not influence surface topographic parameters. Field-mapped channel head locations plot at or downslope from the inflection point of a regional slope-area curve generated from 10 m DEMs, although some extend well downslope. Most actual drainage areas for channel initiation are thus an order of magnitude larger, and plot in a significantly different portion of the slope-area graph, than would result from the widespread practice of assuming channel heads are located at the gradient reversal in such curves.
Covers not scanned.
Keywords: River channels -- Colorado -- Cache la Poudre River Watershed; River channels -- Colorado -- Saint Vrain Creek Watershed; Arid regions -- Colorado -- Cache la Poudre River Watershed; Arid regions -- Colorado -- Saint Vrain Creek Watershed